2010
DOI: 10.1007/s00421-010-1567-7
|View full text |Cite
|
Sign up to set email alerts
|

Practical neck cooling and time-trial running performance in a hot environment

Abstract: The aim of this two-part experiment was to investigate the effect of cooling the neck on time-trial performance in hot conditions (~30°C; 50% RH). In Study A, nine participants completed a 75-min submaximal (~60% V(O₂(max)) pre-load phase followed by a 15-min self-paced time-trial (TT) on three occasions: one with a cooling collar (CC(90)), one without a collar (NC(90)) and one with the collar uncooled (C(90)). In Study B, eight participants completed a 15-min TT twice: once with (CC(15)) and once without (NC(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
104
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(130 citation statements)
references
References 37 publications
12
104
8
Order By: Relevance
“…It is worth noting that wearing the collar uncooled impaired performance compared with the CC trials but had no effect compared with no-cooling, control trials (35). Despite alterations in running performance and capacity, cooling the neck via the practical CC and wearing the collar uncooled had no effect on any of the physiological or neuroendocrinological variables measured (34,35); a result that replicated those reported by previous neck cooling studies (5,13).…”
supporting
confidence: 80%
See 3 more Smart Citations
“…It is worth noting that wearing the collar uncooled impaired performance compared with the CC trials but had no effect compared with no-cooling, control trials (35). Despite alterations in running performance and capacity, cooling the neck via the practical CC and wearing the collar uncooled had no effect on any of the physiological or neuroendocrinological variables measured (34,35); a result that replicated those reported by previous neck cooling studies (5,13).…”
supporting
confidence: 80%
“…As a result, more practical alternatives have been investigated, such as the wearing of a cooling jacket or vest (1,10,11,38) or a cooling collar (CC) (5,13,34,35). Most of these studies have reported that such devices were unable to provide a sufficiently sustained cooling effect to elicit physiological alterations, and this is particularly the case with the neck cooling devices that have been investigated so far (5,13,34,35).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Current modalities used to aid in the prevention, not treatment, of hyperthermia include cooling collars and vests, ice packs and towels, fans, and cold water immersion (DeMartini et al, 2011;Tyler, Wild, & Sunderland, 2010). Additionally, hand cooling devices are unique given the palmar surface area cooled contains vascular networks referred to as arteriovenous anastomoses (Sangiorgi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%